Application of the Concept of Butterfly Edu-Ecotourism as a Manifestation of Real Work Lecture Activities at the Kerandangan Nature Tourism Park: Penerapan Konsep Edu-Ekowisata Kupu-kupu Sebagai Perwujudan Kegiatan Kuliah Kerja Nyata di Taman Wisata Alam Kerandangan - Reginah Fhathonah Insani; Habibah Habibah; Intan Putri Yasa; Lalu Ahmad Azfani; Masnayati Hilmi; Maulidatin Nanisfi; Norma Azizah; Rita Alawiyah; Siti Diniah; Vines Salsa Imami (Jurnal Pengabdian Masyarakat Tropis Indonesia, 2025)
The Real Work Lecture (KKN) in the 2023 Independent Study activity was held at the Kerandangan Nature Tourism Park, Keranganangan Hamlet, Senggigi Village, Batu Layar District, West Lombok Regency. This activity carries the theme "Edu-Ecotourism" and aims to apply the knowledge gained in college in a real context in society. The KKN program consists of main and additional programs. The main program includes socialization of activities and study results to the community, as well as education on the concept of Edu-Ecotourism to children through learning about butterflies and educational competitions. Meanwhile, additional programs include participation in Ramadan Safari activities, takjil distribution, involvement in religious and community events, and Clean Friday activities. All of these activities aim to foster awareness and community involvement in environmental conservation, especially the Kerandangan Nature Tourism Park area. Education to children is expected to be a long-term effort in preserving nature through a fun and community-based approach. This KKN activity was carried out for 5 days with a total time of 40 hours.